2006
DOI: 10.1002/humu.9466
|View full text |Cite
|
Sign up to set email alerts
|

Red cell glucose phosphate isomerase (GPI): a molecular study of three novel mutations associated with hereditary nonspherocytic hemolytic anemia

Abstract: Molecular characteristics of red blood cell (RBC) glucose phosphate isomerase (GPI) deficiency are described in two Spanish patients with chronic nonspherocytic hemolytic anemia. One patient, with residual GPI activity in RBCs of around 7% (GPI-Catalonia), is homozygous for the missense mutation c.1648A>G (p.Lys550Glu) in exon 18. The other patient, with residual activity in RBCs of around 20% (GPI-Barcelona), was found to be a compound heterozygote for two different missense mutations: c.341A>T (p.Asp113Val) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
3
14
1
Order By: Relevance
“…In fact, one of the main characteristics of the mutant dimer is its comparatively low stability. The presented data show that at relatively high temperatures, the mutant enzyme loses activity faster than the wild type, which is in agreement with the reports in hemolysates (12) and cultured fibroblasts from patients affected by the E104D mutation (19,20). Along this line, CD and differential scanning calorimetry data showed that heat denaturation of the wild type occurs at temperatures about 12°C higher than in the mutant enzyme.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In fact, one of the main characteristics of the mutant dimer is its comparatively low stability. The presented data show that at relatively high temperatures, the mutant enzyme loses activity faster than the wild type, which is in agreement with the reports in hemolysates (12) and cultured fibroblasts from patients affected by the E104D mutation (19,20). Along this line, CD and differential scanning calorimetry data showed that heat denaturation of the wild type occurs at temperatures about 12°C higher than in the mutant enzyme.…”
Section: Discussionsupporting
confidence: 81%
“…The data are consistent with TIM activity of affected individuals being substantially lower than in unaffected individuals; it was also shown that TIM activity in the E104D mutant is thermolabile (12,20). A two-hybrid system in yeast was used to explore the interaction between the two monomers of various mutant enzymes, including E104D (21).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Residual GPI activity in erythrocytes of around 7% (GPI-Catalonia), in an individual is homozygous for the missense mutation 1648A→G (Lys550→G l u ) i n e x o n 1 8 w a s d e s c r i b e d and residual activity in erythrocytes of around 20% (GPI-Barcelona), was found in a compound heterozygote for two different missense mutations: 341A→T (Asp113→Val) in exon 4 and 663T→G (Asn220→Lys) in exon 7. Molecular modeling using the human crystal structure of GPI as a model was performed to determine how these mutations could affect enzyme structure and function (Repiso et al, 2006). Chinese hamster (CHO) cell lines with ethylmethane sulfonate induced mutations in GPI and consequent loss of GPI activity have been reported.…”
Section: Point Mutation In Glucose-6-phosphate Isomerasementioning
confidence: 99%